Monitoring Pre- and Post-Operative Immune Alterations in Patients With Locoregional Colorectal Cancer Who Underwent Laparoscopy by Single-Cell Mass Cytometry - Zhou, Chuanyong; Wang, Zaozao; Jiang, Beihai; Di, Jiabo; Su, Xiangqian (Frontiers in Immunology, 2022)
Surgical excision is currently the principal therapy for locoregional colorectal cancer (CRC). However, surgical trauma leads to controlled tissue damage, causing profound alterations in host immunity and, in turn, affecting post-operative outcomes. Surgery-induced immune alterations in CRC remain poorly defined. Here, single-cell mass cytometry was applied to serial blood samples collected pre-operatively, and on days 1, 3, and 7 post-operatively from 24 patients who underwent laparoscopic surgical resection of CRC to comprehensively monitor the peri-operative phenotypic alterations in immune cells and dynamics of immune response. Characterization of immune cell subsets revealed that the post-operative immune response is broad but predominantly suppressive, supported by the decreases in total frequencies of circulating T cells and natural killer (NK) cells, as well as decreased HLA-DR expression on circulating monocytes. The proportion of T cells significantly decreased on day 1 and recovered to the pre-surgical level on day 3 after surgery. The frequency of monocytes was significantly elevated on day 1 after surgery and declined to baseline level on day 3. NK cells temporarily contracted on post-operative day 3. T cells, monocytes, DCs, NK cells, and B cells were partitioned into phenotypically different single-cell clusters. The dynamics of single-cell clusters were different from those of the bulk lineages. T cell clusters in the same response phase fluctuate inconsistently during the peri-operative period. Comparing to the baseline levels, the frequencies of CD11b(+)CD33(+)CD14(+)CD16(−) classical monocytes expanded followed by contraction, whereas CD11b(+)CD33(+)CD14(high)CD16(low) intermediate monocytes remained unchanged; HLA-DR expression in monocytes were significantly reduced; the frequencies of intermediate CD56(bright)CD16(+) NK cell subsets increased; and the percentage of memory B lymphocytes were elevated after surgery. Post-operative pro- and anti-inflammatory cytokines were both altered. Furthermore, peri-operative immune perturbations in some of the cell subsets were unrecovered within seven days after surgery. Chronological monitoring major immune lineages provided an overview of surgery-caused alterations, including cell augments and contractions and precisely timed changes in immune cell distribution in both innate and adaptive compartments, providing evidence for the interaction between tumor resection and immune modulation.